Ameba-associated Microorganisms and Diagnosis of Nosocomial Pneumonia - Berger, Pierre (Centers for Disease Control and Prevention, 2006)
To elucidate the role of ameba-associated microorganisms (AAMs) as etiologic agents of pneumonia, we screened for Legionella spp., Parachlamydia acanthamoeba, Afipia sp., Bosea spp., Bradyrhizobium spp., Mesorhizobium amorphae, Rasbo bacterium, Azorhizobium caulinodans, Acanthamoeba polyphaga mimivirus, and conventional microorganisms in 210 pneumonia patients in intensive-care units by using culture, polymerase chain reaction, and serologic testing. These resulted in 59 diagnoses in 40 patients. AAMs and non-AAMs were implicated in 10.5% of the patients. The infectious agents were identified in 15 patients: Acanthamoeba polyphaga mimivirus, 8; Legionella pneumophila, 3; L. anisa, 1; Parachlamydia sp., 1; Bosea massiliensis, L. worsleiensis, L. quinlivanii, and L. rubrilucens, 1; and M. amorphae and R. bacterium, 1. A. polyphaga mimivirus was the fourth most common etiologic agent, with a higher seroprevalence than noted in healthy controls. This finding suggested its clinical relevance. Therefore, AAM might cause nosocomial pneumonia and should be suspected when conventional microbiologic results are negative.